2019
DOI: 10.3390/atmos10080425
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Mediterranean Tropical-Like Cyclone. Sensitivity to WRF Parameterizations and Horizontal Resolution

Abstract: Due to their rarity and intensity, Mediterranean Tropical-Like Cyclones (TLCs; also known as medicanes) have been a subject of study over the last decades and lately the interest has undoubtedly grown. The current study investigates a well-documented TLC event crossed south Sicily on November 7-8, 2014 and the added value of higher spatial horizontal resolution through a physics parameterization sensitivity analysis. For this purpose, Weather Research and Forecasting model (version 3.9) is used to dynamically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 58 publications
(105 reference statements)
2
22
0
Order By: Relevance
“…More specifically, Matzarakis and Nastos (2011) made an effort to identify heat waves in Athens, Greece, by using the physiologically equivalent temperature (PET), a human thermal index based on the energy balance of the human body. They used consecutive days (three and more) and the duration of each heat wave for PET ≥ 35 • C (the threshold of extreme heat stress; Matzarakis et al, 1999) and T amin ≥ 23 • C (the threshold that represents PET values of thermal neutrality; Nastos and Matzarakis, 2008) in order to quantify the duration of heat waves and their impacts (Fig. 3).…”
Section: Heat Wavesmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, Matzarakis and Nastos (2011) made an effort to identify heat waves in Athens, Greece, by using the physiologically equivalent temperature (PET), a human thermal index based on the energy balance of the human body. They used consecutive days (three and more) and the duration of each heat wave for PET ≥ 35 • C (the threshold of extreme heat stress; Matzarakis et al, 1999) and T amin ≥ 23 • C (the threshold that represents PET values of thermal neutrality; Nastos and Matzarakis, 2008) in order to quantify the duration of heat waves and their impacts (Fig. 3).…”
Section: Heat Wavesmentioning
confidence: 99%
“…Tornadoes occur in many parts of the world (Fujita, 1973). Several publications during the last several decades have presented historical records concerning tornadic activity (e.g., Meaden, 1976;Tooming and Peterson, 1995;Peterson, 1998;Reynolds, 1999;Tyrrell, 2003;Macrinoniene, 2003;Dotzek, 2003;Nastos and Matsangouras, 2010;Gayà et al, 2000;Brázdil et al, 2012;Rauhala et al, 2012;Haghroosta et al, 2014). As far as tornadic activity over Greece is concerned, a comprehensive spatial distribution of a total of 612 events (171 tornadoes, 374 waterspouts and 67 funnel clouds) recorded in 405 d was presented (Matsangouras et al, 2014a, b: Nastos and as there were several days with multiplied events within the period 1709-2012 (Fig.…”
Section: Tornadoes and Waterspoutsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these and other capabilities, the WRF model has been commonly used in recent decades to simulate a wide range of phenomena (Feng et al, 2019;Fernández-González et al, 2018;Hari Prasad et al, 2017;Jandaghian et al, 2018;Martínez-Castro et al, 2019;Skamarock et al, 2008;Vijaya Kumari et al, 2019;Wang et al, 2017;Zhang et al, 2017). Nevertheless, the quality of initial and boundary conditions is a key for accurate cyclones (occurrence and development) simulation (Chutia et al, 2019;Davolio et al, 2009;Mylonas et al, 2019;Ricchi et al, 2017;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The WRF model offers two dynamic solvers for computing the atmospheric governing equations: Advanced Research WRF (ARW) solver and Nonhydrostatic Mesoscale Model. Numerous studies on the WRF numerical model with tropical cyclones have been conducted recently [11][12][13][14][15][16]. For instance, Tao et al [17] indicated that WRF is able to capture the amount and location of the observed surface rainfall and that the typhoon-induced circulation, orographic lifting and a moisture-abundant southwest flow are the main mechanisms that together produced the tremendous rainfall.…”
Section: Introductionmentioning
confidence: 99%